5-hydroxytryptamine is a mediator of 4-aminopyridine induced contractions in porcine and human isolated coronary arteries - Kun, Attila (Acta Biologica Szegediensis, 2000)
The effect of 4-aminopyridine (4-AP), a known inhibitor of voltage-dependent K+ channels (KV), was studied on the resting vasomotor tone in porcine and human coronary arteries. Isolated coronary artery preparations were suspended in organ bath for isometric tension recordings. 4-AP (1.25x10-8 - 5.8x10-4 M) caused concentration-dependent contractions both in porcine and human coronary arteries. The EC50 values obtained with 4-AP did not differ significantly in porcine and human coronary preparations (-4.54 logM and -4.37 logM, respectively). Loading the amine stores of the coronary tissues with 1 mM noradrenalin or blocking the beta-receptors with 2 µM propranolol did not change the contractile effects of 4-AP. In contrast, loading the isolated blood vessels with 1 mM 5-hydroxytryptamine (5-HT) resulted in significantly higher contractions, when induced by micromolar concentrations of 4-AP. The 5-HT receptor blocker, methysergide, almost completely inhibited these contractions. Our present observation provides evidence for the functional role of KV in setting the vasomotor tone of coronary arteries through the release of 5-HT. In the light of these findings we suggest that the porcine coronary artery preparation can serve as a model for studying the functional effect of drugs on KV-type potassium channels.